A feedback system to provide affective support to students. Issue 3 (8th January 2018) - Jiménez, Samantha; Juárez‐Ramírez, Reyes; Castillo, Víctor H.; Licea, Guillermo; Ramírez‐Noriega, Alan; Inzunza, Sergio
Abstract: Learning support systems need to provide direct and affective interaction to students; it can encourage them and improve their motivation to learn. However, several systems do not include this kind of interaction between students and tutors. In those cases, the student learning interest and motivation to learn could be negatively affected, and student profits from the system could be impoverished. Only a few works have examined the influence of written affective feedback, but these studies focused on student learning outcomes, not in student motivation to learn. The objective of this work is to analyze the impact of an affective feedback system on the students' perception of two aspects: (i) the degree to which study time is enjoyable and (ii) the motivation to learn. Results show that the affective feedback system makes more enjoyable study time and motivates students to learn, particularly to students with low academic performance. These system enhancements eventually would improve student‐learning outcomes.